DETERMINATION OF LEAD AND CADMIUM LEVELS IN CANNED SARDINES USING ATOMIC ABSORPTION SPECTROPHOTOMETRY - Makayasa, Citra Hayu Adi; Sumiyani, Ririn; Budiono, Ryanto; Wijaya, Natasha Kezia; Vellisia, Nancy; Umami, Hidayatul (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Canned sardines are hermetically sealed and processed to ensure sterility and provide practical convenience in processing fish. Contact between food and canned causes the migration of metal elements into them. The high content of metals, lead (Pb) and cadmium (Cd) in canned food has a negative impact on health. This study aims to determine both metal levels in canned sardines and to identify the fulfillment of several validation parameters against Atomic Absorption Spectrophotometry (AAS). Sardines were weighed, digested with concentrated HNO3:30% H2O2 and analyzed using AAS. Pb and Cd levels in canned sardines were not detected by AAS. This method meets the requirements of validation parameters, Pb and Cd, selective on specific wavelengths 283.3 nm and 228.3 nm, the standard curve is linear with a relative process standard deviation (Vx0) value < 5% and the Xp value is smaller than the lowest concentration in the standard curve, 0.69 mg/l and 2.31 mg/l are the results of the Limit of Detection (LOD) and Limit of Quantitation (LOQ) values of Pb while Cd 0.20 mg/l and 0.67 mg/l, 80-120% is %recovery of accurate parameters and a relative standard deviation (RSD) value < 2% is precision parameters. The SSA method can be used to quantitatively determine Pb and Cd levels in canned sardines.